HAL YANG RUMPANG DAN TIMPANG DALAM KEBIJAKAN PERENCANAAN BAHASA JAWA - Wahyu Widodo (Masyarakat Linguistik Indonesia, 2017)
There have been five congresses on Javanese language from 1991 to 2011. This indicates that there has been an effort to strengthen the Javanese identity through language engineering programs. There is an assumption that the Javanese people, especially the younger generation, nowadays tend to be monolingual than bilingual (Cohn & Ravindranath, 2014). Is Javanese language internally unable to face globalization challenges, and as a result it suffers from “impotence” and “complication”? (Djatmika, 2010). This article attempts to address the following question: What are the obstacles faced by Javanese language during its process of development? This article is based on the argument that the Javanese language planning through the language engineering program does not incorporate the ‘collective dream’ of its native speakers. The sources of data for this article come from the documents of Javanese congresses I-V and language policy documents pertaining to Javanese language preservation.